Current approaches in image-guided therapy - Jolesz, Ferenc A.; Penzkofer, Tobias (Future Medicine Ltd, 2014)
This book gives an overview of a number of such emerging IGT methods. The editors are pleased to present this bouquet of IR image-guided therapy approaches. The goal of the book is to provide a snapshot of currently developed 'hot' topics in IR, and it is hoped that readers will find it to be comprehensive and encouraging reading on image-guided therapy.